The Influence of Training on the Quality of Employee Work at the Class 1 TPI Makassar Immigration Office - Lembang, Jenni; Bandhaso, Mira Labi; Rasinan, Djusniati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the effect of training on the quality of employee work at the Class I TPI Makassar Immigration Office. Training is an important factor in developing human resource competency, especially in improving public services. This study uses a quantitative approach with the Spearman Rank correlation coefficient analysis method, determination coefficient, and t-test. The results of the study indicate that training has a very strong influence on work quality with a correlation value of 0.956 and a determination value of 0.910, which means that 91% of the variation in work quality is influenced by training. The t-test shows a calculated t value of 13.793> t table 2.101, with a significance of 0.000 <0.05, which indicates a statistically significant effect. Based on these findings, training has been shown to provide a real contribution in improving self-potential, optimal work results, work processes, and employee enthusiasm. Thus, structured and relevant training is an effective strategy in improving the quality of immigration employee work.